MALAYNESS AT THE NEXUS OF NATION AND UMMAH: Rethinking the Cultural Politics of Postcolonial Malay Identity - Khairudin, Fiddian; Anwar, Sudirman (Asia-Pacific Journal on Religion and Society, 2024)
This article seeks to reexamine the trajectory of Malay cultural politics within the broader contestations of identity, religion, and power in Southeast Asia—particularly in Indonesia and Malaysia. Drawing on cultural sociology, Stuart Hall’s theory of cultural representation, Antonio Gramsci’s concept of cultural hegemony, and James Clifford’s notion of “cultural routes,” this study critiques state-driven and puritan Islamic projects that attempt to essentialize and purify Malay identity. Despite its historical formation through centuries of intercultural encounters—including Indian, Arab, Chinese, and maritime-local influences—Malay identity has increasingly been reduced to a homogenized ethno-religious category. Sufi expressions of Islam, customary aesthetics, and localized wisdom are being supplanted by normative-legalist interpretations propagated through state institutions, formal education, and Islamic media networks. Nonetheless, this article also highlights the presence of quiet, grassroots movements that continue to preserve an inclusive and spiritual Islam-Malay heritage, as seen in coastal traditions such as woodcarving, zapin music, hikayat storytelling, and adat practices. The article argues that the future of Malay culture cannot rest upon a singular identity project; rather, it must be grounded in plural expressions, inter-traditional dialogue, and the revitalization of culture as a liberating spiritual space.